The Influence of Leadership and Training on Work Culture and Its Impact on Employee Performance in Halal MSMEs. - Taufik, Azhar; Supyadillah, Asep; Supriyadi, Rinaldi; Willanda Sari, Nova (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2025)
This study was conducted to determine the influence of leadership and training on work culture and its impact on employee performance in Halal UMKM, the case study in this study was at PT Setya Kuliner Mandiri/D’Besto Se-South Tangerang. The method used was a survey method with 86 respondents. Data were collected through questionnaires and analyzed using LISREL. The results of the study showed; 1) leadership has an insignificant influence on work culture of 1.07. 2) training has a significant influence on work motivation of 0.20. 3) leadership has an insignificant influence on employee performance of 1.46. 4) training has an insignificant influence on employee performance of -0.58. 5) work culture has a fairly weak influence on employee performance of -1.65. 6) leadership has a weak influence on employee performance with culture as an intervening of -0.58. 7) training has a weak influence on employee performance with work culture as an intervening of -1.45. 8) work culture is less effective as an intervening variable.